2012
DOI: 10.1111/j.1600-0536.2011.02041.x
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study aimed at finding a suitable eugenol concentration for a leave‐on product for use in a repeated open application test

Abstract: In patients sensitized to eugenol, with the maximum allowed concentration of eugenol and given a prolonged ROAT (4 weeks), there is a clear risk of elicitating an allergic contact dermatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…Although the ROAT was originally recommended for twice daily application for 7 days, 16 more recent studies have shown that a ROAT testing period longer than 7 days may be necessary to identify sensitized patients with a delayed response. 17,18 In a study evaluating linalool, most reactions occurred in the third week, 17 whereas a study with eugenol found most sensitive patients to react in the fourth week. 18 Corticosteroid testing may also require a longer exposure and observation period because the antiinflammatory properties of steroids result in a tendency to suppress immunologic reactions, even in allergic individuals.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although the ROAT was originally recommended for twice daily application for 7 days, 16 more recent studies have shown that a ROAT testing period longer than 7 days may be necessary to identify sensitized patients with a delayed response. 17,18 In a study evaluating linalool, most reactions occurred in the third week, 17 whereas a study with eugenol found most sensitive patients to react in the fourth week. 18 Corticosteroid testing may also require a longer exposure and observation period because the antiinflammatory properties of steroids result in a tendency to suppress immunologic reactions, even in allergic individuals.…”
Section: Discussionmentioning
confidence: 98%
“…17,18 In a study evaluating linalool, most reactions occurred in the third week, 17 whereas a study with eugenol found most sensitive patients to react in the fourth week. 18 Corticosteroid testing may also require a longer exposure and observation period because the antiinflammatory properties of steroids result in a tendency to suppress immunologic reactions, even in allergic individuals. However, nickel may elicit a reaction within 1 week.…”
Section: Discussionmentioning
confidence: 98%
“…When various usage tests including ROATs have been performed with fragrance sensitizers, positive reactions have been obtained in 0–100% of participants . Major reasons for the great variation are the concentration, the actual dose per cm 2 of the applied usage or ROAT preparation, and the length of the application period.…”
Section: Discussionmentioning
confidence: 99%
“…When various usage tests including ROATs have been performed with fragrance sensitizers, positive reactions have been obtained in 0-100% of participants. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Major reasons for the great variation are the concentration, the actual dose per cm 2 of the applied usage or ROAT preparation, and the length of the application period. In the present study, positive ROAT reactions were obtained in 59% of those hypersensitive to FM I and in 3% of those without contact allergy to FM I.…”
Section: Discussionmentioning
confidence: 99%
“…Eugenol is found in soaps, antiseptic solutions and emollient creams used by healthcare workers who frequently wash their hands, dentists are exposed to eugenol in mouthwashes, dressings, impression materials and periodontal packings, eugenol is present in 27% of household products, it is commonly included in cutting fluids used by metalworkers and massage therapists are frequently exposed due to the use of essential oils in their trade [ 124 ]. Recently Svedman et al [ 129 ] evaluated the potential of eugenol to cause allergic contact dermatitis in a repeat open application test (ROAT) for a leave-on product. Five volunteers previously sensitised to eugenol were included in the ROAT study where the maximum allowed concentration of eugenol was applied for 4 weeks.…”
Section: Toxicity and Allergenicity Of Eugenolmentioning
confidence: 99%